Sociological Snapshots 5 : Seeing Social Structure and Change in Everyday Life. - Levin, Dr. Jack (SAGE Publications, 2008)
The Fifth Edition of the best-selling Sociological Snapshots continues to provide a solid foundation for students as it introduces them to the world of sociological analysis. Combining abstract sociological concepts with interesting and grounded essays ("snapshots") on issues of contemporary interest, this book helps students discover relevant connections and encourages them to develop a sociological eye. By linking everyday life experiences to foundational concepts and concerns, it serves as an effective springboard from the student's familiar and concrete world to the more abstract realm of.